Endoglucanase and β-glycosidase activities in an evergreen oak litter: annual variation and regulating factors (Soil Biology and Biochemistry, 2002)
This paper represents the third part of a larger study about the processes involved in litter biodegradation in an oak copse in France. It concerns the variations in activities of endoglucanases and of β-glycosidases over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Q. ilex is the most abundant tree species in forests of the French Mediterranean area. The activities of several endoglucanases and β-glycosidases, and the concentrations of the proteins and reducing sugars were measured in the evergreen oak litter between October 1997 and October 1998. Several biotic and abiotic factors, potentially involved in the regulation of the activities of these hydrolyzing enzymes, were also measured: culturable heterotrophic bacteria, cellulolytic bacteria and cellulolytic fungi, moisture, temperature and pH of the litter. Under this Mediterranean climate, the moisture of the litter was strongly correlated with many factors and is likely to be important in regulating the temporal dynamics of various biological parameters. A multiple regression analysis showed that the annual dynamic of the culturable heterotrophic bacteria was primarily influenced by moisture but also by variations in concentration of reducing sugars in the litter. Moreover, these bacteria were correlated with the activities of several β-glycosidases, and specifically with the N-acetyl-glucosaminidases (r=0.93). No relationships were established between the number of cellulolytic microorganisms (bacteria and fungi) and the activities of endoglucanases (i.e. cellulases and hemicellulases). The seasonal trends of certain biotic processes, and the influence of pH and of temperature on these processes are also discussed. Electrophoretic analyses were used to estimate the number of cellulase and xylanase isoenzymes in the litter, and to study their fluctuations over one year. The prevailing cellulase isoenzyme had a Rf of 0.64, and there was no relationship between the abundance of cellulolytic microorganisms and the electrophoretic profiles of the cellulases. In the case of the xylanases, the electrophoretic profiles were homogenous throughout the year, and the prevailing xylanase had a Rf of 0.75.

Annual variations of phenoloxidase activities in an evergreen oak litter: influence of certain biotic and abiotic factors (Soil Biology and Biochemistry, 2000)
This study concerns ligninolysis phenomena occurring over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Quercus ilex L. is the most abundant tree species in forests of the French Mediterranean area. Several biotic and abiotic factors potentially involved in transformations of polyphenolic compounds, were measured between October 1997 and October 1998. These factors were: global fungal micro¯ora, the fungi producing phenoloxidases (PO+ ), the activities of several phenoloxidases, hydrosoluble phenols, and temperature, humidity and pH of the litter. Results showed that the annual dynamics of fungi and phenoloxidase activities appear to be seasonal, i.e. that these biotic factors such as, were optimal in autumn. A multiple regression analysis showed that there was no correlation between biotic factors such as, fungal populations and phenoloxidase activity and abiotic factors such as, temperature, humidity and pH. Laccases were the preponderant phenoloxidase activities during the year, while those of Mn-peroxidases only appeared in the autumn of 1997. Other phenoloxidases, lignin-peroxidases and tyrosinases were never detected. Interactions between laccases and humic substances were also investigated. Adsorption of laccases on humic substances leads to a shift in the optimal temperature activity of these enzymes from 50 to 308C. Activities of laccases also shifted towards more acidic values when laccases were not adsorbed on humic substances. Nevertheless, the optimal pH was the same (5.7) whether laccases were adsorbed or not to humic substances. Electrophoresis analysis showed little variations in the number of phenoloxidase isoenzymes. Indeed, laccases showed three isoenzymes during the year (Rf 0.23, 0.34 and 0.43). Only one isoform of Mn-peroxidase, with an Rf 0.21, was detected in the litter

Biochemical and molecular characterization of a laccase from Marasmius quercophilus (APPLIED AND ENVIRONMENTAL MICROBIOLOGY, 2000)
The basidiomycete Marasmius quercophilus is commonly found during autumn on the decaying litter of the evergreen oak (Quercus ilex L.), a plant characteristic of Mediterranean forest. This white-rot fungus colonizes the leaf surface with rhizomorphs, causing a total bleaching of the leaf. In synthetic liquid media, this white-rot fungus has strong laccase activity. From a three-step chromatographic procedure, we purified a major isoform to homogeneity, The gene encodes a monomeric glycoprotein of approximately 63 kDa, with a 3.6 isoelectric point, that contains 12% carbohydrate, Spectroscopic analysis of the purified enzyme (UV/visible and electron paramagnetic resonance, atomic absorption) confirmed that it belongs to the ``blue copper oxidase{''} family. With syringaldazine as the substrate, the enzyme's pH optimum was 4.5, the optimal temperature was 75 degrees C, and the K-m was 7.1 mu M. The structural gene, lac1, was cloned and sequenced. This gene encodes a 517-amino-acid protein 99% identical to a laccase produced by PM1, an unidentified basidiomycete previously isolated from wastewater from a paper factory in Spain. This similarity may be explained by the ecological distribution of the evergreen oak in Mediterranean forest.
Keys: APS

Laccase activity of forest litter (Soil Biology and Biochemistry, 1999)
Laccases are blue-copper enzymatic proteins involved in the transformation of polyphenolic compounds, such as lignin, into forest litter. A method to measure their activity was developed using an evergreen oak litter as a model system. We considered factors that aect the extraction of these enzymes and the measurement of their activity. The factors studied included powdering of the leaves, adding polyvinylpolypyrrolidone or Tween 80, adsorption of enzymes on centrifugation pellets, concentration of the extracts, nature and molarity of the extraction solvent, amount of powdered leaves used for enzymatic extraction, extraction time, pH, and temperature during the measurement of the activity

Phenoloxidases of the white-rot fungus Marasmius quercophilus isolated from an evergreen oak litter (Quercus ilex L.) (Enzyme and Microbial Technology, 1998)
A white-rot basidiomycete, Marasmius quercophilus, was isolated from an evergreen oak litter. This fungus, which very thoroughly bleaches the whole leaf area, produces laccases, a property which has not been studied before. Except on a ground leaf medium, we did not reveal phenoloxidases other than laccases. M. quercophilus is able to transform many aromatic compounds which are by-products of lignin and tannin metabolism. We observed, for example, that lignin monomers, namely p-coumaryl, coniferyl, and sinapyl alcohols are oxidized at different rates by the extracellular crude enzyme extract. The highest production of laccases is obtained with shaking cultures on malt extract supplemented with Tween 80 (0.1%) and CuSO4 (0.5 mg l 21 ). These enzymes have an optimum activity at 80°C and a stable activity at 40°C for 18 h. The extracellular crude enzyme extract medium contains three isoenzymes with pI values of 3.8, 3.5, and 3.2. It is able to significantly reduce the kappa number (21.2%) of a kraft pulp without inclusion of any mediator